5.
Пошаговое объяснение:
{х² + 7ху + у² = 35,
{ху = 2;
{х² + 2ху + у² + 5ху = 35,
{(х + у)² + 5ху = 35,
{(х + у)² + 5•2 = 35,
Из первого уравнения системы получим, что
(х + у)² + 10 = 35
(х + у)² = 35 - 10
(х + у)² = 25
l x + yl = √25
l x + yl = 5
ответ: 5.
5.
Пошаговое объяснение:
{х² + 7ху + у² = 35,
{ху = 2;
{х² + 2ху + у² + 5ху = 35,
{ху = 2;
{(х + у)² + 5ху = 35,
{ху = 2;
{(х + у)² + 5•2 = 35,
{ху = 2;
Из первого уравнения системы получим, что
(х + у)² + 10 = 35
(х + у)² = 35 - 10
(х + у)² = 25
l x + yl = √25
l x + yl = 5
ответ: 5.